Informant Discrepancies in Judgments About Change During Mental Health Treatments. (March 2020) - Marsh, Jessecae K.; Zeveney, Andrew S.; De Los Reyes, Andres
Understanding how mental health treatments benefit people who receive treatment comes with a challenge: Often different people involved in treatment have different impressions of the treatment's ultimate effects. How do people reconcile these different reports to understand the true benefit of treatment? In a series of four experiments, we tested people's beliefs about how to integrate information from multiple informants for the treatment improvement of child clients. We found that laypeople (Experiments 1, 2, and 3) and professional mental health clinicians (Experiment 4) trust informants they believe to be insightful about the specific disorder but pessimistic about overall improvement. Our findings suggest important future research avenues to better understand how intuitions about reconciling informants influence the process of weighting information from clients and other people involved in their care.